The Lotus Sutra: A Biography, by Donald S. Lopez, Jr. (30th December 2018) - Jones, Christopher
Abstract : The Lotus Sutra: A Biography, by Donald S. Lopez, Jr. Princeton University Press, 2016. 272pp. Hb. £24.95. ISBN-13: 9780691152202. E-book. £18.99. ISBN: 9781400883349.